A General Approach to O‐Sulfation by a Sulfur(VI) Fluoride Exchange Reaction. (20th August 2020) - Liu, Chao; Yang, Cangjie; Hwang, Seung; Ferraro, Samantha L.; Flynn, James P.; Niu, Jia
Abstract: O‐sulfation is an important chemical code widely existing in bioactive molecules, but the scalable and facile synthesis of complex bioactive molecules carrying O‐sulfates remains challenging. Reported here is a general approach to O‐sulfation by the sulfur(VI) fluoride exchange (SuFEx) reaction between aryl fluorosulfates and silylated hydroxy groups. Efficient sulfate diester formation was achieved through systematic optimization of the electronic properties of aryl fluorosulfates. The versatility of this O‐sulfation strategy was demonstrated in the scalable syntheses of a variety of complex molecules carrying sulfate diesters at various positions, including monosaccharides, disaccharides, an amino acid, and a steroid. Selective hydrolytic and hydrogenolytic removal of the aryl masking groups from sulfate diesters yielded the corresponding O‐sulfate products in excellent yields. This strategy provides a powerful tool for the synthesis of O‐sulfate bioactive compounds. Abstract : Described here is an efficient and broadly compatible early‐stage O ‐sulfation approach based on sulfur(VI) fluoride exchange (SuFEx) chemistry. This strategy provides a powerful tool for the synthesis of O‐sulfate‐containing bioactive compounds.